Pilot evaluation of a novel unilateral onychectomy model and efficacy of an extended release buprenorphine product. Issue 1 (December 2016) - Enomoto, Masataka; Kigin, Patricia; Bledsoe, David; Slone, Robyn; Hash, Jonathan; Smith, Charles; Lascelles, B.
Abstract Background Non-steroidal anti-inflammatory drugs (NSAIDs), transdermal fentanyl patches, and transmucosal buprenorphine are probably the most commonly used options for providing post-operative analgesia in the early at-home period. However, these require daily administration or are associated with abuse concerns. One of the significant unmet needs in veterinary surgery and pain management is for longer acting opioids for cats to effectively bridge the gap between the in-hospital and at-home recovery periods. A proof of concept study of an extended release formulation of buprenorphine HCL (ER-Bup) was conducted using objective kinetic measures and a unilateral onychectomy model. Using a blinded, randomized, two period crossover design, four cats were allocated to control (saline) or ER-Bup (0.6 mg/kg, subcutaneously [SC]) treatment groups. All animals underwent a unilateral forelimb onychectomy per period with a washout/recovery period in between. Observational pain scores and kinetic data (using a pressure sensitive walkway [PSW]) were collected prior to (baseline) and at intervals for 72 h following surgery. Symmetry indices were derived for kinetic variables (peak vertical force [PVF]; vertical impulse [VI]) of each forelimb for landing following a jump and for walking. A rescue analgesic protocol was in place. Effect of surgery and treatment were evaluated using a mixed model statistical approach. Results No cats required rescue analgesics based on subjective pain score. ER-Bup had a positive influence on subjective pain scores during the 72 h postsurgery (p = 0.0473). PVF and VI of the operated limb were significantly decreased for both landing (p < 0.0001 andp < 0.0001) and walking (p < 0.0001 andp < 0.0001 respectively) compared to control. ER-Bup resulted in significantly decreased asymmetry in limb use during landing (PVF, p < 0.0001; VI, p < 0.0001) and walking (PVF, p = 0.0002, VI, p < 0.0001). The novel use of data collected following a jump from an elevated platform appeared to provide all desired information and was easier to collect than walking data. Conclusion This study demonstrates that SC administration of ER-Bup may be an effective analgesic for a 72 h period postoperatively. Furthermore, landing onto a PSW from an elevated perch may be a useful and efficient way to assess analgesics in cats using a unilateral model of limb pain.